Weed Management in Pear - Peter J. Dittmar; Jeffrey G. Williamson (EDIS)
Weeds compete with pear trees for light, nutrients, and water. Weed interference can be minimized with proper cultural practices and herbicides. General maintenance, such as controlling weeds in adjacent areas, preventing weeds from producing seeds, and cleaning mowing equipment of weed seed, will prevent weeds from becoming a serious problem. This revised 6-page fact sheet includes recommendations for herbicides labeled for pear in Florida. Written by Peter J. Dittmar and Jeffrey G. Williamson, and published by the UF Department of Horticultural Sciences, December 2011.